Associations between PTSD symptoms and suicide risk: A comparison of 4-factor and 7-factor models. (October 2020) - Chou, Po-Han; Ito, Masaya; Horikoshi, Masaru
Abstract: Background: While posttraumatic stress disorder (PTSD) symptoms in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) are categorized into four clusters, emerging studies suggest the disorder is best characterized by seven symptom clusters: re-experiencing, avoidance, negative affect, anhedonia, externalizing behaviors, and anxious and dysphoric arousal symptoms. However, data are sparse regarding the relation between this novel model of DSM-5 PTSD symptoms and suicide risk. Methods: Using data from the National Survey for Stress and Health, a sample of 6180 Japanese individuals, we evaluated the relationship between suicide ideation and PTSD symptoms using 4- and 7-factor models. Results: Different association patterns were observed between each model and suicidal ideation. In the 4-factor model, we found re-experiencing feelings (odds ratio [OR] = 1.03, 95% confidence interval [CI] = 1.01–1.06, p = 0.002), negative alterations in cognition and mood symptoms (OR = 1.08, 95%CI = 1.06–1.09, p < 0.001), and hyperarousal (OR = 1.03, 95% CI = 1.01–1.05, p = 0.014) were associated with increased suicide ideation. In the 7-factor model, we found re-experiencing feelings (OR = 1.04, 95%CI = 1.02–1.06, p = 0.001), negative affect (OR = 1.04, 95%CI = 1.01–1.07, p = 0.012), anhedonia (OR = 1.08–1.16, 95%CI, p < 0.001), and externalizing behavior (OR = 1.12, 95%CI = 1.07–1.17, p < 0.001) were associated with increased suicide risk. Conclusions: A more refined 7-factor model of DSM-5 PTSD symptoms may help us understand their associations with comorbid psychopathology and suicide. Prevention and treatment efforts that target distinct aspects of the PTSD phenotype may be more effective in mitigating key clinical and functional outcomes in this population. Highlights: PTSD is best characterized by seven symptom clusters instead of four. A 7-factor model of PTSD symptoms may help us understand their association with suicidal ideation. Targeting distinct aspects of PTSD may be more effective in mitigating patient outcomes.